Bifacial dye-sensitized solar cells using highly transparent PEDOT:PSS films as counter electrodes. (20th February 2015) - Xu, Shunjian; Luo, Yufeng; Liu, Guiwu; Qiao, Guanjun; Zhong, Wei; Xiao, Zonghu; Luo, Yongping; Ou, Hui
Highlights: PEDOT:PSS films were developed as counter electrodes (CE) for bifacial DSSC. PEDOT:PSS films involved a pristine film and 10 modified films. PEDOT:PSS films exhibited transmittances ranging from 78% to 83.5% at 550 nm. IOD, DMSO or PEG200 modified film used in DSSC was superior to pristine film. PEDOT:PSS film used in DSSC had higher CE-illuminated efficiency than Pt electrode. Abstract: Highly transparent poly(3, 4-ethylenedioxythiophene):polystyrenesulfonate (PEDOT:PSS) films prepared by a facile spin-coating process were developed as counter electrodes for the configuration of bifacial dye-sensitized solar cells (DSSCs) with capability of utilizing the light from both sides. The used PEDOT:PSS films involved a pristine PEDOT:PSS film and ten modified PEDOT:PSS ones. The additives for preparing the modified PEDOT:PSS films were involved in iodine (IOD), dimethyl sulfoxide (DMSO), ethanol, acetone, glycerol, sorbitol and poly(ethylene glycol) (PEG) with different molecular weights (200, 400, 800 and 20, 000). The UV–Vis spectra confirm that all the PEDOT:PSS films on fluorine-doped tin oxide substrates have excellent transparency with transmittance ranging from 78% to 83.5% at 550 nm. The bifacial DSSC using the pristine PEDOT:PSS film exhibits the efficiencies of 4.71% and 2.38% corresponding to the illuminations from the front and the rear sides, respectively. When the additives of IOD, DMSO and PEG200 are applied to modify the pristine PEDOT:PSS film, the corresponding device shows a significantly improved efficiency of 5.19%, 5.11% and 5.29% under the front illumination and an almost unchanged efficiency under the rear illumination, respectively. The strengthened efficiency is mainly attributed to the improved catalytic activity of the modified PEDOT:PSS films induced by the coarser surface and the lower sheet resistance. Moreover, the bifacial DSSCs with the three modified PEDOT:PSS films not only have a comparable front-illuminated efficiency to the conventional Pt based DSSCs but also possess a higher rear-illuminated efficiency than the latter cells.